Population-based cross-sectional study to assess newborn hearing screening program in central Germany. (April 2018) - Rissmann, Anke; Koehn, Andrea; Loderstedt, Marja; Schwemmle, Cornelia; Goetze, Gerrit; Bartel, Sylva; Plontke, Stefan K.; Langer, Joerg; Begall, Klaus; Matulat, Peter; Roehl, Friedrich-Wilhelm; Vorwerk, Ulrich
Abstract: Objectives: Early diagnosis of congenital hearing loss is fundamental to minimize the negative consequences on the speech development. To lower the age at diagnosis and at intervention in hearing impaired children, not only universal newborn hearing screening (NHS) but also tracking is considered essential. The aim of the study was to evaluate the first six years after implementation of the population based newborn hearing screening program in Saxony-Anhalt, one German Federal State. Methods: The cross-sectional cohort study consisted of three cohort samples. Overall 102, 301 infants born between January 2010 and December 2015 were included. NHS protocol was developed as dual target group protocol with two sub-protocols. The screening technique included Transient Evoked Otoacoustic Emissions (TEOAE) and Automated Auditory Brainstem Response (AABR) test. Newborns were assigned to the sub-protocols according to their audiological risk factors. Additionally, to evaluate the quality of NHS and tracking (false-negative screening) we were analysing data from a cohort of hearing impaired children diagnosed up to the age of three years. We calculated quality indicators and compared them with international guidelines. Results: 101, 102 (98.8%) infants were screened. The prevalence of bilateral neonatal hearing loss was 2.32 per 1, 000 newborns. The median age was two days at first screening, three month at diagnostic testing, and four month at intervention onset. 2.6% infants were lost to follow-up. 56.3% had a final diagnosis of bilateral sensorineural hearing loss. The sensitivity of 0.85 (KI 95%: 0.76-0.91) and a specificity of 0.84 (KI 95%: 0.84–0.85) was calculated for the NHS program. Conclusion: The analysis of benchmarks and outcomes of NHS demonstrated that the program reaches its main goal to identify the hearing impaired newborns in a timely manner.